2010
DOI: 10.1124/dmd.109.030999
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Metabolism, Permeability, and Efflux of Bazedoxifene in Humans

Abstract: ABSTRACT:Bazedoxifene (BZA) acetate, a novel estrogen receptor modulator being developed for the prevention and treatment of postmenopausal osteoporosis, undergoes extensive metabolism in women after oral administration. In this study, the in vitro metabolism of [ 14 C]BZA was determined in human hepatocytes and hepatic and intestinal microsomes, and the UDP glucuronosyltransferase (UGT) isozymes involved in the glucuronidation of BZA were identified. In addition, BZA was evaluated for its potential as a subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 24 publications
(22 reference statements)
1
23
0
Order By: Relevance
“…For example, for raloxifene, the glucuronidation rates of UGT1A8, UGT1A9, and UGT1A10 are reported to be higher than those of other isoforms (Kemp et al, 2002), which is consistent with our remaining ratio results. Similar consistencies were found with bazedoxifene for UGT1A1, UGT1A8, and UGT1A10 (Shen et al, 2010), diclofenac and gemfibrozil for , and 25.5 ml ⅐ min Ϫ1 ⅐ kg Ϫ1 (C). Solid lines were obtained by fitting with the nonlinear least-squares method.…”
Section: Nakamori Et Alsupporting
confidence: 56%
See 1 more Smart Citation
“…For example, for raloxifene, the glucuronidation rates of UGT1A8, UGT1A9, and UGT1A10 are reported to be higher than those of other isoforms (Kemp et al, 2002), which is consistent with our remaining ratio results. Similar consistencies were found with bazedoxifene for UGT1A1, UGT1A8, and UGT1A10 (Shen et al, 2010), diclofenac and gemfibrozil for , and 25.5 ml ⅐ min Ϫ1 ⅐ kg Ϫ1 (C). Solid lines were obtained by fitting with the nonlinear least-squares method.…”
Section: Nakamori Et Alsupporting
confidence: 56%
“…However, the predicted concentrations in human intestine (Supplemental Data 3) were much higher than 0.1 M, indicating that intestinal glucuronidation should be saturated, which contradicts the linearity of oral AUC increases. For example, a previous study found that K m values of bazedoxifene for intestinal microsomes-5.1 (bazedoxifene-4Ј-glucuronide) and 5.1 M (bazedoxifene-6Ј-glucuronide) (Shen et al, 2010)-were lower than the predicted intestinal concentration (25-170 M) at oral doses ranging from 3 to 20 mg (Supplemental Data 3); however, oral AUC values were reported to increase in proportion to oral doses from 5 to 120 mg (Supplemental Data 2). This contradiction may be explained by autoactivation and gut volume.…”
Section: Nakamori Et Almentioning
confidence: 99%
“…In the case of eslicarbazepine acetate, in vivo drug interaction studies were preemptively performed with two known P-gp inhibitors, cyclosporine and verapamil, and no interaction was observed in either study. For bazedoxifene, in vitro screening studies have been published previously (Shen et al, 2010), thus no studies were included in the filing. Out of the 12 positive P-gp in vitro results, 7 in vivo studies were performed, with the largest interaction observed in the case of sofosbuvir (AUC ratio = 3.6, when coadministered with cyclosporine).…”
Section: Preclinical Drug Interaction Datamentioning
confidence: 99%
“…A combination of conjugated estrogens with bazedoxifene has been evaluated in a 2-year clinical trial and found to be effective in treatment of hot flushes without untoward effects to date (51). Bazedoxifene does not stimulate the proliferation of MCF-7 cells, although it has a very low bioavailability relative to conjugated estrogens (52), and long-term effects on breast tissue are not known.…”
Section: Discussionmentioning
confidence: 98%